Modulation of Cytokines and Extracellular Matrix Proteins Expression by Leishmania amazonensis in Susceptible and Resistant Mice - Cardoso, Flávia de Oliveira; Zaverucha-do-Valle, Tânia; Almeida-Souza, Fernando; Abreu-Silva, Ana Lúcia; Calabrese, Kátia da Silva (Frontiers in Microbiology, 2020)
Leishmaniases are a complex of diseases with a broad spectrum of clinical forms, which depend on the parasite species, immunological status and genetic background of the host. In the L. major model, susceptibility is associated with the Th2 pattern of cytokines production while resistance is associated with Th1 response. However, the same dichotomy does not occur in L. amazonensis-infected mice. Cytokines are key players in these diseases progression, while the extracellular matrix components participate in the process of parasite invasion as well as lesion healing. In this article, we analyzed the influence of host genetics on the expression of cytokines, iNOS and extracellular matrix proteins, as well as the parasite load in mice with different genetic backgrounds infected by L. amazonensis. C57BL/10 and C3H/He mice were subcutaneously infected with 106 L. amazonensis promastigotes. Lesion kinetics, parasite load, cytokines, iNOS and extracellular matrix proteins expression were measured by qPCR in the footpad, draining lymph nodes, liver and spleen at early (24h and 30 days) and late phase (120 and 180 days) of infection. Analysis of lesion kinetics showed that C57BL/10 mice developed ulcerative lesions at the inoculation site after L. amazonensis infection, while C3H/He showed slight swelling in the footpad 180 days after infection. C57BL/10 showed progressive enhancement of parasite load in all analyzed organs, while C3H/He mice showed extremely low parasite loads. Susceptible C57BL/10 mice showed high levels of TGF-β mRNA in the footpad early in infection and high levels of proinflammatory cytokines mRNA (IL-12, TNF-α and IFN-γ) and iNOS in the late phase of the infection. There is an association between increased expression of fibronectin, laminin, collagen III and IV and TGF-β. On the other hand, resistant C3H/He mice presented a lower repertory of cytokines mRNA expression when compared with susceptible C57BL/10 mice, basically producing TNF-α, collagen IV and laminin early in infection. The findings of our study indicate that L. amazonensis infection induces different cytokine expression in resistant and susceptible mice, but not like the L. major model. An organ-compartmentalized cytokine response was observed in our model. Host genetics determine this response, which modulates extracellular matrix proteins expression.